Islamic Banking and Financial Crisis: The Case of Pakistan a Qualitaive Approach - Khataw, Nazish (2010)
Since the Credit Crunch of 2007-08, a lot of academic and popular literature has focused on the strengths of Islamic banks in the face of financial crises. It is interesting to find out why the developing countries such as Pakistan weren‟t affected by the financial crisis. This paper explores the theory behind these claims by examining how the Islamic financial system increases market self-discipline by sharing the risks equitably between banks and depositors. It is found that this approach reduces moral hazard, asymmetric information and speculation, as well as reduces the different risks that banks face. This paper also establishes a relationship between risk management and business performance, especially in the face of a financial panic. There has been very little literature provided on the credit crunch affecting the Islamic Banks of Pakistan. This paper focuses its study here for two reasons: first, there are opportunities to compare and contrast Islamic banks with conventional banks; second, why wasn‟t the Islamic Banking sector of Pakistan affected by the financial crisis which makes for a fascinating case study. By analysing the interviews taken at few Islamic banks this study will be carried on. It will talk about the future of Islamic Banks in Pakistan as well. Qualitative research method has been used with a narrative approach. Quantitative data such as annual reports have been used for financial analysis.